THE BEHAVIOR OF CATTLE FARMERS ON THE FEED SUPPLY IN DRY SEASON IN SAMBIRENTENG VILLAGE, DISTRICT OF TEJAKULA, BULELENG REGENCY - A. R., Zodyanto; Inggriati, N. W. T.; Suarta, G. (Jurnal Peternakan Tropika; Vol 10 No 1 (2022): Vol. 10 No. 1 Tahun 2022; January - april, 2022)
This study aims to determine the behavior of cattle farmers in providing feed in the dry season and the factors associated with the behavior of farmers. This research was conducted in Sambirenteng Village, Tejakula District, Buleleng Regency. The research was carried out for three months, from February to April 2021. The selection of research locations and the determination of respondents used the Purposive Sampling method, as many as 35 respondents who are cattle farmers with a minimum of two cows and have been raising cattle for at least 5 years. Data analysis was carried out by means of qualitative descriptive and Spearman's Level Correlation Coefficient test. The results of the study 1) knowledge and skills are included in the low category while attitudes are included in the positive category; 2) Factors related to behavior are cattle ownership, land area controlled, age, formal education, non-formal education and participation in farmer/livestock groups; while the experience of raising livestock is not related to the behavior of farmers. Conclusions: 1) The behavior of farmers is low in providing forage feed in the dry season; 2) Factors related to behavior include: cattle ownership, land area controlled, age, formal education, non-formal education and participation in farmer/livestock groups. Suggestion: the government to be more active in providing counseling or training to farmers about providing feed in the dry season, to be able to improve the behavior of farmers. Keywords: knowledge, attitudes, skills, forage, counseling